Tip dependence of three-dimensional scanning force microscopy images of calcite-water interfaces investigated by simulation and experiments - Miyazawa, K.; Tracey, J.; Reischl, Bernhard; Spijker, P.; Foster, A.S.; Rohl, Andrew; Fukuma, T. (ROYAL SOC CHEMISTRY, 2020)
© 2020 The Royal Society of Chemistry.